Dirac–Hartree–Fock Perturbation Calculation of Magnetic Shielding Using the External Field-Dependent Restricted Magnetic Balance Condition - Hamaya, Satoru; Fukui, Hiroyuki (Bulletin of the Chemical Society of Japan, 2010)
A formulism for four-component Dirac–Hartree–Fock perturbation theory using the restricted magnetic balance (RMB) condition with gauge-including atomic orbitals (GIAOs) is derived at an ab initio level. In this formulation, the zeroth-order Dirac–Hartree–Fock equations are subject only to the usual restricted kinetic balance (RKB) condition, while the external field-dependent RMB condition is introduced in the calculation of the first-order magnetically perturbed orbitals. The magnetic shielding can be divided into a paramagnetic part and a diamagnetic part, as for nonrelativistic (NR) shielding. The present theory is applied to the calculation of hydrogen halide and molecular halogen shieldings.